2004
DOI: 10.1071/sr02006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of increasing salinity and 15N-labelled urea levels on growth, N uptake, and water use efficiency of young tomato plants

Abstract: A greenhouse experiment was conducted to investigate the response of tomato plants (Lycopersicon lycopersicum L.) to salinity and to determine the interactive effects of salinity and nitrogen fertilisation on yield, nitrogen uptake, water use efficiency (WUE), and root-zone salinity during early plant growth. Furthermore, the effects of salinity and N fertilisation were evaluated by measurement of carbon isotope discrimination (Δ). Tomato plants were grown in pots filled with 8 kg (dry weight equivalent) of Kr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 31 publications
1
7
1
Order By: Relevance
“…This result further demonstrated that the reasonable nitrogen application rate (135 kg N ha -1 ) could alleviate the interactive effects on post-anthesis reproductive growth under both water deficit and saline soil conditions. Similar phenomenon was reported by Xue et al, (2007) and Kütük et al, (2004), who suggested that increasing the nitrogen fertilizer supply to a certain extent could attenuate the interactive effects of water-salt stress on sunflower and tomato development, respectively.…”
Section: Discussionsupporting
confidence: 87%
“…This result further demonstrated that the reasonable nitrogen application rate (135 kg N ha -1 ) could alleviate the interactive effects on post-anthesis reproductive growth under both water deficit and saline soil conditions. Similar phenomenon was reported by Xue et al, (2007) and Kütük et al, (2004), who suggested that increasing the nitrogen fertilizer supply to a certain extent could attenuate the interactive effects of water-salt stress on sunflower and tomato development, respectively.…”
Section: Discussionsupporting
confidence: 87%
“…There are many reports associating improvement of WUE with N supply (Heitholt, 1989; Pieterse et al, 1997Brück et al, 2001; Brueck andSenbayram, 2009;Kütük et al, 2004). However, in this experiment, the increase in supply of fertilizer N and the accompanying increase in N%, showed no relation to WUE, which remained static (Fig.…”
Section: Discussioncontrasting
confidence: 48%
“…Past many researches show that an increase in N supply accompanies an increase in WUE (Heitholt, 1989;Pieterse et al, 1997;Brück et al, 2001;Kütük et al, 2004;Brueck and Senbayram, 2009). However, WUE is lower in nodulated plants with a high concentration of internal N (Unkovich and Pate, 2000;Sumi et al, 2005).…”
mentioning
confidence: 99%
“…Some researchers have evaluated the effects of N application on tomato (Lycopersicon esculentum Mill.) (Kutuk et al, 2004) and cotton (Gossypium hirsutum L.) (Chen et al, 2010;Dong et al, 2012) under salinity stress, and found that N application improved yield (Chen et al, 2010). The data from 3 yr of field trials indicated an almost linear relationship between N application rates and yields of L. chinensis in both MSSL and SSSL conditions (Tables 3 and 5).…”
Section: Discussion Nitrogen Application Restrainsmentioning
confidence: 92%